PENGARUH KOMPENSASI, LINGKUNGAN KERJA DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA DAN TURN OVER INTENTION (STUDI PADA KARYAWAN MNC BANK WILAYAH SUMATERA) - Rukmini, Emma; Hendriani, Susi (Jurnal Tepak Manajemen Bisnis, 2017)
This research was conducted in MNC Bank Sumatera region. The purposeof this study was to determine the effect, directly or indirectly variable compensation,work environment and career development to job satisfaction and turnoverintention.This study population by 135 people who are employees of MNC Bank ofSumatera. Selection of the sample conducted with random sampling. Variables used arecompensation, work environment and career development as the dependent variable, turnoverintention as an independent variable .The results of this experiment showed thatcompensation has a direct impact on job satisfaction and turnover intention. The resultsshowed that analysys path reduces job satisfaction is able to turn over intention, as wellas compensation, work environment and career development can improve job satisfactionand lower turnover intention.